HUBUNGAN TINGKAT PENDIDIKAN IBU DENGAN PEMILIHAN METODE KONTRASEPSI DIDESA JAMBEARUM KECAMATAN PASRUJAMBE KABUPATEN LUMAJANG - Wulandari, Eka Yusnia; Indriati, Ina; Maulina, Rifzul (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
The selected effective contraceptive method is the use of tools or methods to prevent pregnancy for an extended period, especially recommended for couples who do not wish to have more children and have high effectiveness (95%) when used properly and regularly. Selected effective contraceptive methods consist of several types; however, the community is not well-informed about these various contraceptive methods and lacks understanding in selecting the appropriate contraceptive method to use. This research aims to determine the relationship between the maternal education level and the choice of family planning contraceptive methods in Jambearum Village, Pasrujambe District, Lumajang Regency. This research is an analytical observational study using a cross-sectional design with a quantitative approach. A sample of 52 respondents was taken using purposive sampling technique. Data analysis was conducted using the chi-square test. The results of the research revealed that nearly half of the respondents had an elementary education level, with 21 respondents (40.4%). Furthermore, 49 respondents (94.2%) made appropriate choices in family planning. From the chi-square test analysis, the obtained value of α was 0.023, indicating that α < 0.05, thus it can be concluded that there is a relationship between the maternal education level and the choice of family planning contraceptive methods in Jambearum Village, Pasrujambe District, Lumajang Regency. It is essential to improve access to and education about various effective contraceptive methods among rural communities and increase access to education for women to support informed choices regarding their reproductive health.